Integrasi Akupunktur dan Herbal dalam Sistem Kesehatan Kota Surakarta: (Review Literatur dan Peluang Penguatan Kebijakan Publik) - Nita Aryani; Richana Richana; Wirda Rohmah (Jurnal Bengawan Solo Pusat Kajian Penelitian dan Pengembangan Daerah Kota Surakarta, 2026)
This study examines the integration of acupuncture and herbal medicine into the health system of Surakarta City through a literature review of regulations, service practices, and the socio-cultural dynamics that shape community acceptance. The analysis shows that the integration of traditional health services, particularly acupuncture and herbal medicine, has strong relevance to community health needs while aligning with Surakarta’s cultural identity, which has long embraced jamu traditions and traditional healing practices. The findings indicate that this integration has the potential to enhance community quality of life by expanding therapeutic options, increasing cultural comfort, and strengthening promotive and preventive health efforts. Furthermore, opportunities within the creative economy, especially those related to herbal-based products and traditional health services, provide broader contributions for local micro-enterprises, traditional health practitioners, and the health-tourism sector. This integration can serve as a bridge between modern healthcare and cultural heritage, fostering a holistic approach to well-being. Nevertheless, the integration process continues to face challenges, particularly in regulatory frameworks, service quality, and the need for professional training to meet modern health standards. Addressing these challenges is essential to ensure the sustainable integration of acupuncture and herbal medicine into the city’s health system, with potential positive impacts on both public health and local economic growth.